Contribution of exome sequencing to the identification of genes involved in the response to clopidogrel in cardiovascular patients. (20th March 2020) - Fontana, Pierre; Ibberson, Mark; Stevenson, Brian; Wigger, Leonore; Daali, Youssef; Niknejad, Anne; Mach, François; Docquier, Mylène; Xenarios, Ioannis; Cuisset, Thomas; Alessi, Marie‐Christine; Reny, Jean‐Luc
Abstract: Background: On‐clopidogrel platelet reactivity (PR) is associated with the risk of thrombotic or bleeding event in selected populations of high‐risk patients. PR is a highly heritable phenotype and a few variants of cytochrome genes, essentially CYP2C19, are associated with PR but only explain 5% to 12% of the variability. Objective: The aim of this study is to delineate genetic determinants of on‐clopidogrel PR using high‐throughput sequencing. Methods: We performed a whole exome sequencing of 96 low‐ and matched high‐PR patients in a discovery cohort. Exomes from genes with variants significantly associated with PR were sequenced in 96 low‐ and matched high‐PR patients from an independent replication cohort. Results: We identified 585 variants in 417 genes with an adjusted P value < .05. In the replication cohort, all top variants including CYP2C8, CYP2C18, and CYP2C19 from the discovery population were found again. An original network analysis identified several candidate genes of potential interest such as a regulator of PI3K, a key actor in the downstream signaling pathway of the P2Y12 receptor. Conclusion: This study emphasizes the role of CYP‐related genes as major regulators of clopidogrel response, including the poorly investigated CYP2C8 and CYP2C18.